ANALYSIS OF THE INFLUENCE OF PROMOTIONS AND PRICES ON INTEREST IN PURCHASING SATYA SANTOSHA PRODUCTS IN DENPASAR CITY - Swara, Ega Paudra; Sumaji, Yoseva Maria Pujirahayu (PERFORMA, 2024)
This research was conducted to determine and analyze the influence ofpromotions and prices on purchasing interest. This research uses quantitativemethods with the population used being people who consume chicken meat inDenpasar City aged 16 to 60 years. The number of samples used was 120 people.The sampling technique was carried out using the purposive sampling method. Theresults of the research that has been carried out find that the promotion variablehas a significant ef ect on buying interest and the price variable has a significantef ect on buying interest.